If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = -83 + -7 Reorder the terms: 7 + 3x = -83 + -7 Combine like terms: -83 + -7 = -90 7 + 3x = -90 Solving 7 + 3x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = -90 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = -90 + -7 3x = -90 + -7 Combine like terms: -90 + -7 = -97 3x = -97 Divide each side by '3'. x = -32.33333333 Simplifying x = -32.33333333
| 0.83w=10 | | 2v-8-2=(12v+4)+7(2v-10) | | 4y^2-13y-12=0 | | 6x-2=3(x-1)+1 | | -10=6y | | s=c+m | | 5-7x=137-35x | | 56w=10 | | .667(.875+4x)-.125=.875 | | -u-7+8u+(-3u)= | | 5x^2+6x-1224=0 | | 13-11w=3-e | | 225x+50625=900x+13500 | | -42-2=8-7x | | 4+3y=12+12y | | 4y^2-5= | | -6-3u+9-(-4u)= | | 68-5x=8x+15 | | 7p-14=-2p+11 | | -4y+8-2-y=6 | | A+30.6=C+26.5 | | 19-p-14=-2p+11 | | 9x-7x+1=8 | | u+(-10u)+(-4)-(-1)= | | -(p-8)-4p=8-4p | | 25w-96=25w-27 | | 7t-14-16t+9c+(-14)= | | -8x=2x+10 | | (2x^2)+15x-12=1 | | 25=5*x | | 2x^2+15x-12=1 | | 2x^2+15x-12=0 |